A study on ER stress-induced apoptosis pathway in cervical cancer HeLa cells treated with biosynthesized gold nanoparticles - Kamala Priya, M. R. (2023)
In the present study, the biosynthesized gold nanoparticles, nanoconjugates, nano-dox conjugate, chitosan–nano-dox conjugate were treated against cervical cancer HeLa cell line. The results demonstrated anticancer effects of the nanocompounds implying nanoparticles induced apoptotic pathway in the cancer cells. Further apoptotic expression was studied for six major apoptotic proteins such as Caspase 12, Bcl 2, BAX, Cytochrome c, PARP3 and Mcl 1. The present study was focussed on anticancer efficiency of biosynthesized nanomaterials.